The possibility of Malaysia allowing dual citizenship: a case study / Nurhidayah Abdul Karim ... [et al.] - Abdul Karim, Nurhidayah; Husna Syed Ahmad Taufek, Sharifah NurHidayatul; Jamil, Nur Azreen; Kasim, Nurul Fatma Hidayah (2014)
This research encompasses the study of law of citizenship in Malaysia specifically on the possibility of Malaysia granting dual nationality to the citizens. Malaysia has long implemented single nationality and this is entrenched in Article 24 of the Federal Constitution which deals with the termination of Malaysian citizenship in the event when a person acquired his second nationality. Not only that, Part III, Chapter 2 of the Federal Constitution further provides the provisions which states that dual citizenship is strictly prohibited in Malaysia. However, dual nationality is seen as a necessity to some Malaysians these days for them to improve their mobility and thus, bearing in mind that the law must not stand still, this research aims on seeking the possibility of Malaysia granting dual nationality whilst considering the advantages and disadvantages of it besides instigating the thoughts of Malaysian citizens themselves on the issue discussed.